Evaluating community-based disaster preparedness programs: a case study from Semeru area - Wafiqotul Jamilah (CV Narasi Khatulistiwa Indonesia, 2026)
Background: Communities residing in high-risk volcanic zones continue to experience uneven disaster preparedness despite formal mitigation programs, highlighting the need for evaluation-oriented engagement. Objective: This program aimed to evaluate and strengthen community-based disaster preparedness in villages surrounding Mount Semeru through participatory and reflective approaches. Method: A participatory model was implemented involving evaluation activities, refresher training, and sustained mentoring with community members, local institutions, and disaster management stakeholders. Results: The program improved residents’ preparedness knowledge, evacuation competence, and response confidence, while fostering collective practices such as local drills and peer learning, alongside improved institutional alignment through community-informed evacuation plans. Implication: These findings suggest that evaluation-driven and participatory approaches can enhance community ownership and effectiveness of disaster preparedness in high-risk areas. Novelty: The program introduces an evaluation-centered, trauma-sensitive model that integrates local knowledge with formal disaster governance as a transferable framework for disaster-prone contexts.